Shape-selective oriented cerium oxide nanocrystals permit assessment of the effect of the exposed facets on catalytic activity and oxygen storage capacity - Sreeremya, Thadathil S.; Krishnan, Asha; Remani, Kottayilpadi C.; Patil, Kashinath R.; Brougham, Dermot F.; Ghosh, Swapankumar (ACS Applied Materials & Interfaces, 2015)
The catalytic performance of a range of nanocrystalline CeO2 samples, prepared to have different morphologies, was measured using two accepted indicators; oxygen storage and diesel soot combustion. The same powders were characterized hi detail by HR-TEM, XRD, XPS, and Raman methods. The study demonstrates that activity is determined by the relative fraction of the active crystallographic planes, not by the specific surface area of the powders. The physical study is a step toward quantitative evaluation of the relative contribution to activity of the different facets. The synthetic protocol permits fabrication of CeO2 nanostructures with preferentially grown active planes, and therefore has potential in developing catalytic applications and in nanocompositing.
Keywords: ceria; chemical activities; crystal facets; nanocrystals; texture coefficient